Quality of life, life satisfaction and happiness in shift- and non-shiftworkers - Lipovcan LJ Kaliterna; Larsen Z Prizmic; N Zganec (Universidade de São Paulo, 2004)
OBJECTIVE: To investigate the quality of life, life satisfaction, happiness and demands of work in workers with different work schedules. METHODS: The survey was carried out on professional workers in social care. Some were shiftworkers whose schedule included night shifts (N=311), some were shiftworkers without night shifts (N=207) and some were non-shiftworkers (N=1,210). Surveys were mailed and the response rate was 86%. For the purpose of this study several variables were selected from the Survey: The Quality of Life Profile, which measures importance, satisfaction, control and opportunities in nine domains of life plus measures of happiness, life satisfaction and demands of work. RESULTS: While both groups of shiftworkers, compared to non-shiftworkers, reported needing more physical effort to complete their work, and reported 'being' more physically tired, no differences were found in reports of overall happiness, life satisfaction or total quality of life. However, night-shiftworkers reported greater percentage of time unhappy than the other two groups of workers. In analyses of the quality of life, night-shiftworkers were less satisfied with domains of spiritual 'being' and physical and community 'belonging' than day-shiftworkers and non-shiftworkers. They also reported having fewer opportunities to improve their physical 'being', leisure, and personal growth than the other two groups. CONCLUSIONS: Quality of life in specific domains in night-shiftworkers was rated worse than in other groups of workers. Domain-based quality of life assessment gives more information regarding the particular needs of workers than overall or global measures of well-being. OBJETIVO: Estudar a qualidade de vida, satisfação pessoal, felicidade e exigências do trabalho entre trabalhadores com diferentes horários de trabalho. MÉTODOS: Realizou-se uma pesquisa entre profissionais da área de assistência social. Alguns trabalhavam em turnos noturnos (N=311) e diurnos (N=207), e outros não trabalhavam em turnos (N=1.210). O questionário da pesquisa foi enviado por correio e a taxa de resposta foi de 86%. Para o estudo, foram selecionadas variáveis incluídas no Perfil de Qualidade de Vida, que mede a importância, satisfação, controle e oportunidades em nove domínios da vida, além de medir a felicidade, satisfação pessoal e exigências do trabalho. RESULTADOS: Em comparação com os trabalhadores que não trabalham em turnos, ambos os grupos de trabalhadores em turnos informaram precisar fazer um esforço físico maior para completar o trabalho e "sentir" um cansaço físico maior. Entretanto, não foram encontradas diferenças nos relatos de felicidade global, satisfação pessoal e qualidade global de vida. Os trabalhadores de turnos noturnos relataram, no entanto, passar um maior tempo infelizes em relação aos outros dois grupos de trabalhadores. As análises de qualidade de vida revelaram que os trabalhadores de turnos noturnos sentiam-se menos satisfeitos nos domínios de "ser" espiritual e "pertinência" física e comunitária que os trabalhadores diurnos e os que não trabalhavam em turnos. Também informaram ter menos oportunidades de aperfeiçoar o seu "ser" físico, lazer e crescimento pessoal em comparação com os outros dois grupos. CONCLUSÕES: A qualidade de vida em domínios específicos em trabalhadores noturnos foi classificada como pior do que em outros grupos de trabalhadores. A qualidade de vida baseada em domínios proporciona maiores informações relativas às necessidades particulares dos trabalhadores se comparada a medidas globais do bem-estar.